If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12n-6(1-9n)=4(10n-5)
We simplify the equation to the form, which is simple to understand
-12n-6(1-9n)=4(10n-5)
Reorder the terms in parentheses
-12n+(-6+54n)=4*(10n-5)
Remove unnecessary parentheses
-12n-6+54n=+4+*(+10n-5+)
Reorder the terms in parentheses
-12n-6+54n=+(+40n-20)
Remove unnecessary parentheses
-12n-6+54n=+40n-20
We move all terms containing n to the left and all other terms to the right.
-12n+54n-40n=-20+6
We simplify left and right side of the equation.
+2n=-14
We divide both sides of the equation by 2 to get n.
n=-7
| -11(12+p)=-2p+8(p-8) | | 7-7x=155-35x | | 5y-(-2y)= | | 10n-27=63 | | (N-6)*10=20 | | 4-2.5= | | (N-6)*10=10 | | 68-4x=5x+17 | | -3y+2=-13 | | 59a+4=36 | | 3x+1=(x-9) | | (2x+3)(2x+5)(x-1)(x-2)=30 | | -10t-2=0 | | -10t^2-2t=0 | | 4x-(3x+7)=-1 | | 2x+3x-2=98 | | 5(4x-6)-8=6x-24 | | 2x^2+9*x-7=0 | | x-22=4 | | x+5+133+x= | | x^3+4x^2+5x+2=0 | | 3(5a-2)-2a+10= | | 3(n-1.8)=2n+1 | | 6(x-1)-2(2-x)=8-(2-6x) | | x^4+4x^3+5x^2+2x=0 | | q*(5-q)= | | 3y=-28-x | | 2(1+x)-1=3(2x+1)+2 | | z-48=-32 | | (5-q)-5q= | | 8x-1/5-1=(50-2x/9)+(3x+3/4) | | 16x+7x+15=0 |